1989
DOI: 10.1007/bf00266717
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic versus open synovectomy in the rheumatoid knee

Abstract: We report the clinical and radiological results after arthroscopic synovectomy (41 knees) and open capsulosynovectomy (26 knees) in patients with rheumatoid arthritis, with an average follow-up of more than ten years. The clinical outcome was much the same in both groups, but there was gradual deterioration, especially after eight years. Radiological changes of osteoarthritis were worse in the knees treated by open capsulosynovectomy compared with the arthroscopic group. Arthroscopic synovectomy has many advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 5 publications
3
23
0
1
Order By: Relevance
“…Many studies have demonstrated that synovectomy can effectively relieve the symptom and improve the function of the affected joints because of removing actively inflamed synovium [1][2][3][4]. Open synovectomy is the traditional effective surgery in treating chronic synovitis.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that synovectomy can effectively relieve the symptom and improve the function of the affected joints because of removing actively inflamed synovium [1][2][3][4]. Open synovectomy is the traditional effective surgery in treating chronic synovitis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of arthroscopic synovectomy in rheumatoid arthritis allows the removal of inflamed synovium with minimal morbidity and decreased hospital stay [6]. Ogilvie-Harris has reported the results of arthroscopic synovectomy on 96 knees with rheumatoid arthritis, with 76% of knees being free from moderate or severe synovitis and with a significant reduction of pain at 4-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies using the open technique are well documented but few papers describing the arthroscopic technique involve studies longer than 5 years [8]. The advantages of the arthroscopic technique include small scars resulting in a more rapid postoperative rehabilitation, and some reports record a greater postoperative range of movement [6,12]. Disadvantages include technical difficulties in accessing certain areas of inflamed synovium in the knee and are associated with a steep learning curve for this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the arthroscopic synovectomy is the preferred operation due to faster recovery, which reduces the duration of hospital stay and enables the earlier recovery of function in the operated joint, with the resultant effect of less postoperative pain, less bleeding and excellent cosmetic effect. [66][67][68] Some of the literature contains conflicting reports of the clinical results of rheumatoid knee synovectomy. In 1988, A controlled multi-centre evaluation of open surgical synovectomy in the treatment of RA was carried out over a period of 5 years after the operation.…”
Section: Kneementioning
confidence: 99%